The historical supernovae - Clark, David H.; Stephenson, F. Richard (Francis Richard), 1941- (Pergamon international library of science, technology, engineering, and social studies., 1977)
The Historical Supernovae is an interdisciplinary study of the historical records of supernova. This book is composed of 12 chapters that particularly highlight the history of the Far East. The opening chapter briefly describes the features of nova and supernova, stars which spontaneously explode with a spectacular and rapid increase in brightness. The succeeding chapter deals with the search for the historical records of supernova from Medieval European monastic chronicles, Arabic chronicles, astrological works etc., post renaissance European scientific writings, and Far Eastern histories and.